Training in Competition Speed Intensity and in the Light of the Motor Energy Law to Develop the Physical-physiological Abilities and the 400m Run for the Youth - Jebur Al-Majidi, Abdulrazzaq; Saleh Fathi, Rafia; Al Fadhly, Sareeh (International Journal of Psychosocial Rehabilitation, 2020)
The 400-meter run is one of the competitions that is recognized by high speed at its final stages with the aim of breaking world records. This certainly emphasizes the development of the physical abilities related to power, speed, endurance, and competition speed through special exercises. This necessitates the researchers manipulating a new method to define new training intensity for the 400m runners according to the competition speed, which is restricted to the speed covered by the competitor throughout the race. This is also restricted to a deliberate scientific planning to define the training intensity according to the pace of ability law. This is intended to impact the development of some special physical & physiological abilities to achieve this competition. The researchers believe that this method has not been employed before, and the results of analyzing the times of the partial distances were not considered practical. This is directly conducive to improving performance and building a special, trustworthy training philosophy to develop the competitor’s ability. This is done by entire reliance on the results of the competition speed rate of each competitor during the race; this is called "competition speed or competition pace," along with the motor energy law as a strategy to gain a good position. The research was applied to a specimen of young track and field competitors in Baghdad. The researchers applied the special speed tests, speed endurance tests, and some other physiological parameters. Training sessions were applied for 10 weeks as 3 sessions per week. The researchers concluded that there was a vital development in speed endurance and competition speed endurance, partial times development for each competition in addition to the development of the physiological parameters and performance.